School Counsellor's Perception of Multicultural Guidance and Counseling - Yosef Yosef; Fadhlina Rozzaqyah; Sigit Dwi Sucipto (STAI Hubbulwathan Duri, 2022)
Having a deep multicultural perception is a must for school counsellors who serve students from diverse cultural backgrounds. Describing their perception of the importance of multicultural guidance and counselling is the main objective of this study. Fifty middle and high school counsellors participated in this study. Data of their perception were collected by administering a 10-item questionnaire in an online version which requires them to respond on a scale of 1-10, ranging from not important to important, encompassing cognitive, affective, and practice dimensions. The main findings of this study revealed that school counsellors have similar perceptions on the importance of multicultural guidance and counselling either in cognitive, affective, or practice dimensions, according to demographic data categories of gender, age, and years of experience. The significant difference is only found as they are categorized into middle and high school counsellors.